Correction: Huynh et al. Spike Protein Impairs Mitochondrial Function in Human Cardiomyocytes: Mechanisms Underlying Cardiac Injury in COVID-19. Cells 2023, 12, 877 - Tin Van Huynh; Lekha Rethi; Ting-Wei Lee; Satoshi Higa; Yu-Hsun Kao; Yi-Jen Chen (Cells)
There was an error in the original publication [...]